5x-3(4x-3)=8x-7(3x-1)

Simple and best practice solution for 5x-3(4x-3)=8x-7(3x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3(4x-3)=8x-7(3x-1) equation:



5x-3(4x-3)=8x-7(3x-1)
We move all terms to the left:
5x-3(4x-3)-(8x-7(3x-1))=0
We multiply parentheses
5x-12x-(8x-7(3x-1))+9=0
We calculate terms in parentheses: -(8x-7(3x-1)), so:
8x-7(3x-1)
We multiply parentheses
8x-21x+7
We add all the numbers together, and all the variables
-13x+7
Back to the equation:
-(-13x+7)
We add all the numbers together, and all the variables
-7x-(-13x+7)+9=0
We get rid of parentheses
-7x+13x-7+9=0
We add all the numbers together, and all the variables
6x+2=0
We move all terms containing x to the left, all other terms to the right
6x=-2
x=-2/6
x=-1/3

See similar equations:

| y2+-10y-4X+21=0 | | 5p-Q=25 | | 3y+4=5y+4 | | 4^(x-8)=64 | | 1200*((1.05^x)/(0.05))=5172.15 | | 1200*((1.05^x-1)/(0.05))=5172.15 | | 10^x=1/10 | | 1200*((1.05^x-1)/(0.05)=5172.15 | | 6+x=8+2 | | 4z+12-4=81/2z+8 | | y=16+4 | | x+0,49x=244,24 | | 4x=3=-5 | | (x^2)+4x-200=0 | | -2a+-1a-1=36 | | 5+3•x=35 | | 3b+5b-2-8=17 | |  6d+8=14+3d6d+8=14+3d | | 3(2x-5)-16+5x=-8(3x-1)+2x+9 | | (8x^2)+20x-208=0 | | 50+10•x=70 | | 20+7•x=83 | | 8x+22=4x+42 | | -2(2-4x)+3-4x=6(x+2)-14x+5 | | 2(6x^2+3x-1)=0 | | -4×(3+5w)=-8 | | 7-x-4=10 | | -x-12=5x=36 | | 5-10x-16=7-5x+3 | | 9x^2-125/5=4x | | 2(x-4)-4(x-5)=12 | | x-3=6-4 |

Equations solver categories